Heart Rate Monitoring During Behavioral Stress Tests in Bold and Shy Rainbow Trout (Oncorhynchus mykiss) - Eleftherios Kasiouras; Gautier Riberolles; Albin Gräns; Andreas Ekström; Johan Höjesjö; Jonathan A. C. Roques; Erik Sandblom; Lynne U. Sneddon (Fishes)
Monitoring stress in captive fish is crucial for their welfare, but continuous physiological measures in unrestrained animals are challenging. Rainbow trout (Oncorhynchus mykiss) exhibit divergent personalities, ranging from bold to shy, which correlate with cortisol-mediated stress responses. To determine whether personality affects the sympathetic nervous system, heart rate was measured during three potentially stressful events as a proxy for sympathetic nervous system responses. Firstly, trout were classified as bold or shy, using a novel object test. Subsequently, trout were implanted with biologgers to record heart rate in vivo at rest during and after the behavioral tests. Following recovery, the fish underwent a second novel object test, a confinement test, a pair-wise contest, and a final novel object test to explore the degree of boldness over the experimental period, which remained consistent. Heart rate was relatively higher in both bold and shy animals during the confinement test and the pair-wise contest compared with the novel object test, which indicated that heart rate monitoring was a valid gauge of the valence of the experience. Heart rate responses did not differ between bold and shy trout, indicating that behavioral phenotype did not influence the autonomic stress response. Thus, heart rate is a reliable indicator of stress without the need to account for intra-specific behavioral variations.